CUTTING AND THRUST FORCES IN FACE TURNING OF TI6AL4V UNDER VARIOUS CUTTING ENVIRONMENTS - Uysal, Alper (YILDIZ TECHNICAL UNIV, 2021)
Ti6Al4V alloys are widely applicable in aerospace, military, automotive, medical etc. industries due to their inherent properties such as high temperature resistance, high strength to weight ratio, dimensional stability, great corrosion endurance etc. However, there are some challenges on machining of Ti6Al4V because of their high hardness, elevated cutting temperature at cutting zone, chemical reaction between cutting tool and workpiece. For these reasons, the studies related to machining of these alloys have been conducting. In the presented experimental study, face turning tests were performed on Ti6Al4V alloy under dry, minimum quantity lubrication (MQL) and cryogenic (liquid nitrogen, LN2) conditions at various cutting speeds. During machining experiments, cutting and thrust forces were measured. Based on the force results, the cutting forces reduced with increase of the cutting speed in three cutting environments. Additionally, the minimum cutting forces were achieved under MQL condition whereas the maximum cutting forces were obtained under dry cutting.
Keywords: Ti6Al4V; face turning; cutting forces; cryogenic; MQL; TOOL LIFE; TI-6AL-4V; HYBRID; ALLOY; WEAR; Engineering